How To Development of Pop Up Book Media To Improve Literacy In Tsunami Disaster Mitigation For Elementary School Students? - Yoga Marga Mahendra; Risky Dwi Cahya; Herwin (Postgraduate, University of Mataram, 2023)
This research aims to create a Pop Up book about disasters and assess how good and useful it is as a learning tool. This type of research is Research and Development (R&D), using a five-stage ADDIE development model, namely analysis, design, development, implementation, and evaluation.Â The method used in this study used interview methods, questionnaires. The data collection instruments used are questionnaire sheets, and multiple choice tests. The validation assessments for the Pop Up Book media involved experts, with the media expert assessment at 69.4, considered